HUMAN CAPITAL AND VERTICAL SKILL MISMATCH: THE CASE OF THE NEW EU MEMBER STATES FROM EASTERN EUROPE - Neycheva, М. (PUBLISHINGS of Kostanay State Pedagogical University, 2018)
he purpose of this study is to shed light on the link between human capital and vertical mismatch in the 11 new EU member states from Eastern Europe. Human capital is measured by the percentage of the active population having completed higher education. In the economies under consideration both the number of tertiary education graduates and the degree of the skill mismatch have been sharply increasing since the year 2000. The rate of the job mismatch appears to be positively influenced by the share of female graduates. On the other hand, it is negatively linked to the gross value added of the trade-related services.
Keywords: human capital; higher education; skill mismatch; labor market; new EU member states